New species and new records of Glyptoma Erichson, 1839 (Coleoptera: Staphylinidae) - Klemann-Junior, Louri; Moura, Roberta Souza De; Irmler, Ulrich; Asenjo, Angélico (Zootaxa, 2025)
We described three new species of the genus Glyptoma Erichson, 1839 (Coleoptera: Staphylinidae: Osoriinae), G. curupira Klemann-Junior, Moura, Irmler & Asenjo, sp. nov., G. luae Klemann-Junior, Moura, Irmler & Asenjo, sp. nov. and G. malkini Irmler, Klemann-Junior, Moura & Asenjo, sp. nov., from Amazonas and Pará states, in the north of Brazil. We illustrated major diagnostic features and integrated the new species into the key to Glyptoma species published by Irmler (2015). Furthermore, we provided new records of G. amazonense Irmler 2015, G. denieri (Bernhauer 1939), G. klimschi (Bernhauer 1908), G. lescheni Irmler 2015, and G. nitidum (Bernhauer 1908) for Brazil, and G. cicatricosa Motschulsky 1857 for French Guiana.